On a classification of finite dimensional algebras with respect to the orthogonal (unitary) changes of basis - Bekbaev, Ural (Institute of Physics Publishing, 2016)
In this paper, we consider a classifcation, with respect to the orthogonal (unitary)change of basis, of fnite dimensional algebras. A fnite system of invariants, which separates nonequivalent algebras, whose systems of structural constants are from an invariant, open, dense set, is given.